The Effect of Relational Models on the customer engagement Value: Evidence from the Hospitality Industry - Fahimeh Vahabzadeh; Samad Aali; Alireza Bafandeh Zendeh; Houshang Taghizadeh (Muṭāli̒āt-i Mudīriyyat-i Gardishgarī, 2020)
Companies working in a competitive environment are increasingly facing challenges in attracting and retaining customers. In this regard, companies try to create superior value for customers compared to competitors and in return, expect customers to participate in creating value for the company. But customers are different and use different relational models to interact with companies, which affect the amount and type of engagement they make in creating value for companies. Therefore, in the present article, we look at the extent to which customer relational models influence their engagement in creating value for hotels, and each customer involved in the creation of what kind of value. To this end, loyal customers of five-star hotels in the northwest of the country were selected as the statistical population and 533 customers participated in the research by completing the questionnaire. A convenience sampling method was used to select the statistical sample. In terms of the aim of the research, this is applied research and in terms of methodology, this is casual research. The research hypotheses were tested using structural equation modeling technique and AMOS software. Findings show that customers who use a non-social relational model in their interaction with the hotel participate in creating three types of value (lifetime value, influence value, and knowledge value) for the hotel and customers with relational models of communal sharing and equality matching create value for the hotel, through knowledge and impact on others respectively in addition to providing a lifetime value. Ultimately, customers with market pricing models create value for the hotel only by offering their lifetime value.